A PELE POR TRÁS DA MÁSCARA: a representação de super-herois negros da Marvel e da DC nas telas dos cinemas - Mendonça, Hector Lucas Sousa (2024)
Movies based on superhero comic books have experienced notable growth since the early 2000s. However, when examining the bodies that star in these productions, we rarely see Black skin as central characters. In the 2010s and 2020s (up to the present moment), there have been only five films released in theaters starring Black superhero characters, with four of them being male. Motivated by these observations, this research seeks to investigate how the representation of these Black protagonists unfolds, aiming to uncover whether these few characters are Black by deliberate choice and whether other bodies could occupy that place, or if these characters are Black because they necessarily need to be, considering the history constructed around them, as well as potential constructions of characters around stereotypes imposed on Black men over time. In this empirical trajectory, we propose to build methodological guidelines based on authors in Cultural Studies and related fields who discuss race and ethnicity, specifically bell hooks, Frantz Fanon, Grada Kilomba, Homi Bhabha, and Stuart Hall. The research focuses on male protagonists, also reflecting on how these Black men are represented. In addition to the aforementioned authors, the research also investigates other works by Brazilian authors who study Black masculinity in the media.